The Preservation of the Terbang Papat Music at Ash-Shiddiqin Musalla in Kudus Regency - Ryandana, Mylza Nova; Florentinus, Totok Sumaryanto; Utomo, Udi (Catharsis, 2020)
Terbang Papat is a typical traditional art from Kudus, the name of Terbang Papat was taken from the instruments of Terbang in the amount of four and used one Jidor. The art of Terbang Papat, now is starting to fade because it has been replaced by the times. This study aims to provide a preservation overview of the Terbang Papat art form in Kudus. The study was conducted by using a qualitative analysis research method with the research location in the Kedungdowo Kaliwungu village, Kudus Regency. The data collection techniques used observation, interviews, and document study. The data validity technique used data triangulation technique. Meanwhile, data analysis and processing techniques were carried out by collecting, reducing, clarifying and verifying data. The result of preserving the Terbang Papat music is from musical elements namely the time element and the characteristics of the accompanying instruments.